Pendampingan Teknis Teknologi Tepat Guna Budidaya Udang Vaname Skala Kecil di Desa Pengambengan, Jembrana, Bali - Ilham; Insani, Liga; Wahyu; Abrori, Mohsan; Sudiarsa, I Nyoman; Kusmiatun, Anik; Nisa, Andina Chairun; Aras, Annisa Khairani; Jatayu, Diklawati; Kiswanto, Arie; Utami, Diah Ayu Satyari (Institut Pertanian Bogor, 2024)
Pacific white shrimp (Penaeus vannamei) is one of Indonesia's fishery commodities with high economic value in the domestic and foreign markets. They are applying appropriate technology through small-scale shrimp farming aimed to transfer technology in partner villages from traditional to intensive systems. This program was an effort to improve the welfare of the fishery community in Desa Pengambengan, Jembrana, Bali. This program was carried out in May‒July 2022, and it involved the Mina Jaya Fish Cultivator Group as the target community. The activity program was carried out through several stages, including audience activity, counseling, technical assistance, and monitoring and evaluation. The activity succeeded in increasing the knowledge and skills of the target community regarding vaname shrimp cultivation in detail. Technical assistance for cultivation activities has increased community understanding of small-scale intensive shrimp cultivation, minimizing errors and increasing program success. Monitoring and evaluation are carried out to determine the sustainability of activities in the target community. This community service activity has succeeded in increasing the productivity of Pacific white shrimp cultivation and technology transfer from the traditional system to a small-scale intensive system.